2022
DOI: 10.1089/whr.2021.0130
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Cross-Sectional Survey of Anesthesiology Fellowship Program Directors: Attitudes on Parental Leave in Residency and Fellowship Training

Abstract: Introduction: Little is known about the impact of parental leave on anesthesiology fellowship directors' perception of their fellows. In addition, use of parental leave during residency can result in “off-cycle” residents applying for a fellowship. This study sought to clarify fellowship directors' attitudes and beliefs on effects of parental leave on fellows and off-cycle fellowship applicants. Methods: An online survey was sent to anesthesiology fellowship program dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…For example, a study of anesthesiology fellowship programs found more had written policies about maternity than paternity leave. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of anesthesiology fellowship programs found more had written policies about maternity than paternity leave. 10…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of anesthesiology fellowship programs found more had written policies about maternity than paternity leave. 10 Among respondents who had experienced infertility, length and demands of training were commonly believed to have contributed to infertility. Up to 60% of female residents delay childbearing because of training, 11 and many Mohs surgeons are over 30 years old by the time they complete training.…”
Section: Discussionmentioning
confidence: 99%